UJI TOKSISITAS DAN IDENTIFIKASI AWAL GOLONGAN SENYAWA AKTIF EKSTRAK ETANOL DAN N-HEKSANA TERIPANG PASIR (Holothuria scabra) KERING PANTAI KENJERAN SURABAYA - Inayah, Nurul; Ningsih, Rachmawati; Adi, Tri Kustono (ALCHEMY, 2012)
Sea cucumber (H.Scabra)is a species of marine biota providing high economicaland medical values. It has been hundreds years consumed for drug to cure various diseases in China. The aim of this research was to determine the level of the toxicity against brine shrimp larvae A.salina Leach in each dried sea cucumber (H.scabra) extract collected from Kenjeran Coast, Surabaya. The information would be beneficial for anticancer drug discovery .The research was conducted by extracting samples using both ethanol and n-hexane solvents.The concentrated extract obtained then were used for the toxicity test against brine shrimp larvae of A.salina Leach (BSLT). The mortality data of A.salina Leach was analysed using probit analysis to determine the value of LC50 on each extract. The phytochemical assay and thin layer chromatography (TLC) was also apllied for both extracts.The result showed that both ethanol and n-hexane exctracts performed toxicity level against brine shrimp larvae of A.salina Leach with LC50less than 1000 ppm.The n-hexane extract indicated LC50 of 189.093 ppm, higher than the ethanol extract, 286.031 ppm. The presence of steroids were detected in both extract whilst the alkaloids were only detected in the ethanol extract. Further separation of the n-hexane exctrat using TLC in n-hexane;ethyl acetate;amonia (66:33:0.8) yielded 5 spots with the Rf of 0.3;0.44;0.54;0.72 and 0.78, respectively.